44Ti self-diffusion in nanocrystalline thin TiO2 films produced by a low temperature wet chemical process. (May 2018) - Straumal, P.B.; Stakhanova, S.V.; Wilde, G.; Divinski, S.V.
Abstract: Grain boundary self-diffusion of titanium in nanocrystalline TiO2 films is investigated in an extended temperature interval by the radiotracer technique applying the 44 Ti isotope. The diffusion annealing treatments are performed at low and high oxygen partial pressures. At low oxygen partial pressure Ti grain boundary self-diffusion follows an Arrhenius type temperature dependence with the pre-exponential factor of 7.25 × 10 −12 m 2 /s and the activation enthalpy of 74.7 kJ mol −1 . At high oxygen partial pressure Ti diffusion follows an Arrhenius type temperature dependence below 773 K and changes drastically the behavior above 773 K indicating a possible grain boundary structure transition. Graphical abstract: Unlabelled Image